Deep Soil Layers of Drought-Exposed Forests Harbor Poorly Known Bacterial and Fungal Communities - Frey, Beat; Walthert, Lorenz; Perez-Mon, Carla; Stierli, Beat; Köchli, Roger; Dharmarajah, Alexander; Brunner, Ivano (Frontiers in Microbiology, 2021)
Soil microorganisms such as bacteria and fungi play important roles in the biogeochemical cycling of soil nutrients, because they act as decomposers or are mutualistic or antagonistic symbionts, thereby influencing plant growth and health. In the present study, we investigated the vertical distribution of the soil microbiome to a depth of 2 m in Swiss drought-exposed forests of European beech and oaks on calcareous bedrock. We aimed to disentangle the effects of soil depth, tree (beech, oak), and substrate (soil, roots) on microbial abundance, diversity, and community structure. With increasing soil depth, organic carbon, nitrogen, and clay content decreased significantly. Similarly, fine root biomass, microbial biomass (DNA content, fungal abundance), and microbial alpha-diversity decreased and were consequently significantly related to these physicochemical parameters. In contrast, bacterial abundance tended to increase with soil depth, and the bacteria to fungi ratio increased significantly with greater depth. Tree species was only significantly related to the fungal Shannon index but not to the bacterial Shannon index. Microbial community analyses revealed that bacterial and fungal communities varied significantly across the soil layers, more strongly for bacteria than for fungi. Both communities were also significantly affected by tree species and substrate. In deep soil layers, poorly known bacterial taxa from Nitrospirae, Chloroflexi, Rokubacteria, Gemmatimonadetes, Firmicutes and GAL 15 were overrepresented. Furthermore, archaeal phyla such as Thaumarchaeota and Euryarchaeota were more abundant in subsoils than topsoils. Fungal taxa that were predominantly found in deep soil layers belong to the ectomycorrhizal Boletus luridus and Hydnum vesterholtii. Both taxa are reported for the first time in such deep soil layers. Saprotrophic fungal taxa predominantly recorded in deep soil layers were unknown species of Xylaria. Finally, our results show that the microbial community structure found in fine roots was well represented in the bulk soil. Overall, we recorded poorly known bacterial and archaeal phyla, as well as ectomycorrhizal fungi that were not previously known to colonize deep soil layers. Our study contributes to an integrated perspective on the vertical distribution of the soil microbiome at a fine spatial scale in drought-exposed forests.